The good earth - Buck, Pearl S (Oxford University Press, 1993)
This book is adapted from novel The good earth a the story of the cyclical nature of life, of the passions and desires that motivate a human being, of good and evil, and of the desire to survive and thrive against great odds. It begins with the story of an illiterate, poor, peasant farmer, Wang Lung, who ventures from the rural countryside and goes to town to the great house of Hwang to obtain a bride from those among the rank of slave.